THE IMPLEMENTATION AND IMPROVISATION OF ISLAMIC SCHOOL CURRICULUM IN BUDDHIST COUNTRY - Wijayanti, Fantri Agustin; Widhanarto, Ghanis Putra (Indonesian Journal of Curriculum and Educational Technology Studies, 2019)
Thailand is one of the greatest Buddhist country in Southeast Asia, therefore the Buddhism values and culture inevitably intervene education, including the curriculum. It is interesting to investigate how Islamic school arranges and develops its own curriculum in order to balance the national interest influenced by Buddhism and the Islamic belief, values, and culture owned by the school in Thailand. This article tries to illustrate Anuban Islam Songkhla School as one of the Islamic schools adapts the national educational policy and arranges their curriculum rooted on Islamic vision. This research found that Songkhla School does not implement all policy endorsed by the government officially due to its incompatibility with the Islamic vision of the school.    Abstrak Thailand adalah salah satu negara Budha terbesar di Asia Tenggara, oleh karena itu nilai-nilai dan budaya Budha tak terelakkan lagi pasti mengintervensi dunia pendidikannya, termasuk kurikulumnya. Sangat menarik untuk menyelidiki bagaimana sekolah Islam di Thailand mengatur dan mengembangkan kurikulumnya sendiri untuk menyeimbangkan kepentingan nasional yang dipengaruhi oleh agama Budha dengan ajaran, nilai-nilai, dan budaya Islam yang dimiliki oleh sekolah tersebut. Artikel ini mencoba menggambarkan Sekolah Songkhla Islam Anuban sebagai salah satu sekolah Islam yang mengadaptasi kebijakan pendidikan nasional dalam upaya menyusun kurikulum mereka sendiri yang berakar pada visi-visi keislaman. Penelitian ini menemukan bahwa Sekolah Songkhla tidak menerapkan semua kebijakan yang diberlakukan oleh pemerintah secara resmi, karena memang pada dasarnya tidak semuanya kompatibel dengan visinya sebagai sekolah Islam.